FAKTOR – FAKTOR YANG MEMPENGARUHI KEBIJAKAN HUTANG PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (Students' Journal of Accounting and Banking, 2015)
In the application of the debt are also prone to interest between shareholders. Debt policy conflict between managers and creditors arises when managers take on projects that have a greater risk than that estimated by the lender. This research to analyze the effect of institutional ownership structure, managerial ownership, profitability, dividend policy, free cash flow, and the size of debt to equity ratio. The population in the penilitian this is a manufacturing company which is registered in BEI of 149 enterprises. By using purposive sampilng technique that is a manufactuing company delivering a complete financial statement data during the period of observation and research variables related to the number of samples obtained 19 companies. Analysis tools are used Multiple Liner regression anaysis, where the normality tests previously done and tests the assumptions classical. The results showed that institutioal ownership has no effect against teh policy of debt, can be interpreted as that the smaller the proportion of institutional ownership, than it does not effect the debt policies. This is caused  because the proportion of institutional ownership is small so less powerfull in controlling internal to the company so as not to effect teh policy conducted the managements in using debt. Managerial ownership structural, profitability and dividend policy and significant negative effect against debt policy. While free cash flow and the size of the company has a positive and significant influence towards debt policy.Keywords: Ownership Structures Institutional, Ownership Structures Managerial, Profitability, Policy Dividend, Free Cash Flow, Size, Debt to Equity Ratio